The effect of perceived usefulness, perceived ease of use, and complexity upon the acceptance of computerized audit technique (ACAT) at the Finance and Development Supervisory Agency (FDSA) Republic of Indonesia - Blasius Fembriyanto Trisno Saputro; Gideon Oki Manalu (STIE Binaniaga, 2019)
Perceived Usefulness (PU) in matters relation of the dimensions of enhanced performance and productivity will make the auditors use the Acceptance of computerized audit technique (ACAT). Perceived Ease of Use (PEOU), through their knowledge, ease of operation, and the need for the work that is free from businesses that facilitate the use of information systems being used will make the auditors Acceptance of ACAT. Complexity is a hassle on infrastructure and the required time factor affecting the use of Acceptance of ACAT. Results of this study are carried out through the delivery of questionnaires to the auditor at the Finance and Development Supervisory Agency (FDSA), confirm that there is significant Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) against Acceptance of ACAT and Complexity makes the auditors didn’t Acceptance of ACAT. Keywords: Perceived Usefulness, Perceived Ease of Use, Complexity, Acceptance of ACAT